2022
DOI: 10.1039/d2na00188h
|View full text |Cite
|
Sign up to set email alerts
|

Templated electrodeposition as a scalable and surfactant-free approach to the synthesis of Au nanoparticles with tunable aspect ratios

Abstract: A high-throughput method for the fabrication of ordered arrays of Au nanoparticles is presented. It is based on pulsed electrodeposition into porous anodic alumina templates. In contrast to many synthesis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“…5). 84 Compared to colloidal fabrication approaches, the electrochemical synthesis technique can be applied for manufacturing NPs without surfactants or capping agents to stabilize their sizes and morphologies, paving the way to construct NPs as catalysts without restrictions in their reactive surface sites; this method can also be applied for synthesizing NPs with a controllable inter-pore distance. However, the limitation of this technique was its low yield of production, and future explorations ought to be focused on its up-scalability along with optimization conditions.…”
Section: Surfactant-free Synthesis Of Metal and Metal Oxide Nanomater...mentioning
confidence: 99%
See 3 more Smart Citations
“…5). 84 Compared to colloidal fabrication approaches, the electrochemical synthesis technique can be applied for manufacturing NPs without surfactants or capping agents to stabilize their sizes and morphologies, paving the way to construct NPs as catalysts without restrictions in their reactive surface sites; this method can also be applied for synthesizing NPs with a controllable inter-pore distance. However, the limitation of this technique was its low yield of production, and future explorations ought to be focused on its up-scalability along with optimization conditions.…”
Section: Surfactant-free Synthesis Of Metal and Metal Oxide Nanomater...mentioning
confidence: 99%
“…However, the limitation of this technique was its low yield of production, and future explorations ought to be focused on its up-scalability along with optimization conditions. 84 It was revealed that the particle size can be controlled by adjusting the current density and the distance between electrodes. 43 In one study, the particle size of magnetite NPs increased by enhancing the current density and reducing the distance between electrodes; the particle formation could not be favored when the distance between electrodes was larger than a critical value.…”
Section: Surfactant-free Synthesis Of Metal and Metal Oxide Nanomater...mentioning
confidence: 99%
See 2 more Smart Citations
“…Specically, templated electrodeposition provides a versatile method to fabricate well-dened nanostructures. 17,18 Commercial tracketched polycarbonate membranes and porous anodic aluminium oxide membranes with vertical pore channels and >20 nm pore sizes are the most commonly used templates for electrodeposition. Silica thin lms have excellent insulation and thermal stability properties, and are widely used as a dielectric material.…”
Section: Introductionmentioning
confidence: 99%